Magnetic transition metal sulfide adsorption material as well as preparation method and application thereof

By constructing a MoS2/C composite material and loading Fe3O4, the problems of low adsorption capacity and MOF framework in existing adsorbents during gold recovery were solved, achieving efficient adsorption and reduction of Au3+, and realizing rapid separation of materials and integrated synergy of photoresponsive separation and photoresponsiveness.

CN121060465APending Publication Date: 2025-12-05JINGGANGSHAN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511390572.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing adsorbents suffer from low adsorption capacity, poor selectivity, and slow adsorption rate when recovering gold. In particular, they are subject to severe interference from coexisting ions in complex aquatic environments, and the coordination bonds of MOF materials are unstable in aquatic environments, leading to framework hydrolysis and collapse.

Method used

Using Mo-MOF as a precursor, stable Mo-S bonds are constructed by optimizing the material ligands to form a MoS2/C composite material. Fe3O4 is loaded on the surface of MoS2/C to endow the material with magnetic and photoresponsive properties. By utilizing the strong reducing power of MoS2 and the photothermal conversion ability of Fe3O4, the efficient adsorption-reduction-magnetic separation-photoresponsiveness of Au3+ is achieved in an integrated synergistic manner.

Benefits of technology

It achieves efficient and selective adsorption and reduction of Au3+ in water. The material can be rapidly separated from water, improving adsorption capacity and adsorption rate. It solves the problem of framework hydrolysis and collapse of MOF with unstable coordination bonds in the water environment, and meets the needs of gold resource recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121060465A_ABST
    Figure CN121060465A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorbent materials, and particularly relates to a magnetic transition metal sulfide adsorption material and a preparation method and application thereof. The preparation method comprises the following steps: by taking Mo-MOF as a precursor, calcining a sulfur source and the Mo-MOF at 1000-1100 DEG C under a protective atmosphere, carbonizing a ligand in the Mo-MOF to form a porous carbon matrix, performing a vulcanization reaction on the sulfur source and Mo < 3 + > to form MoS2 particles, and embedding the MoS2 particles into the porous carbon matrix to obtain MoS2 / C; a chemical coprecipitation method is adopted, Fe3O4 magnetic nanoparticles are loaded on the surface of MoS2 / C, and the magnetic transition metal sulfide adsorption material is obtained. The prepared magnetic transition metal sulfide adsorption material can efficiently and selectively adsorb and reduce Au < 3 + > in a water body, rapid separation can be carried out through magnetism, and resource recycling of gold is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of adsorbent materials technology, specifically relating to a magnetic transition metal sulfide adsorbent material, its preparation method, and its application. Background Technology

[0002] Au (Au) is a valuable precious metal widely used in the electronics industry, catalysis, sensors, and energy devices due to its excellent electrical conductivity, ductility, and chemical stability. However, gold resources are non-renewable, and traditional ore mining cannot meet the ever-increasing industrial demand. At the same time, the amount of electronic waste is increasing dramatically, representing a significant potential gold resource. Failure to efficiently recover gold from waste electronic products will not only result in resource waste but also cause serious environmental problems.

[0003] In the pretreatment of electronic waste, hydrometallurgical leaching solutions are an important source for gold recovery. Currently, methods for recovering gold from gold-bearing water bodies include solvent extraction, electrochemical reduction, chemical precipitation, ion exchange, membrane filtration, coagulation, and adsorption. Among these, solvent extraction and electrochemical reduction are complex, costly, and require expensive reagents; chemical precipitation is prone to secondary pollution; and ion exchange and membrane filtration technologies have high equipment requirements and significant operating and maintenance costs. In contrast, adsorption methods are widely studied due to their simplicity and lower cost, and are considered to have the potential for large-scale application. However, existing adsorbents generally suffer from low adsorption capacity, poor selectivity, and slow adsorption rates, especially in complex aquatic environments where coexisting ions cause severe interference, significantly affecting the efficiency and purity of gold recovery.

[0004] MOF materials, due to their high specific surface area and tunable pore structure, are suitable for Au. 3+ Exhibiting excellent affinity, MOFs are considered to be a promising adsorbent material. However, the dynamic instability of the coordination bonds between most MOFs and ligands in aqueous environments can easily lead to framework hydrolysis and collapse, resulting in the deactivation of active sites and the degradation of adsorption performance. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a magnetic transition metal sulfide adsorbent material, its preparation method, and its applications. This material can efficiently and selectively adsorb and reduce Au in water. 3+ It can be rapidly separated by magnetism, realizing the resource recovery of gold; it solves the technical problem of framework hydrolysis and collapse caused by unstable coordination bonds in the water environment of MOF in the prior art.

[0006] This invention uses Mo-MOF as a precursor and constructs more stable Mo-S bonds by optimizing the material ligands, serving as a preform for Au adsorption. 3+The core active component was used to obtain a MoS2 / C composite material; simultaneously, Fe3O4 was loaded onto the MoS2 / C surface, endowing the material with magnetic and photoresponsive properties, enabling the material to rapidly separate from water within minutes using an external magnetic field; and its own photothermal conversion capability was utilized to enhance the material's adsorption capacity; ensuring efficient and selective adsorption of Au in water. 3+ At the same time, it solved the technical problem of framework hydrolysis and collapse of MOFs in aquatic environments due to unstable coordination bonds.

[0007] The first objective of this invention is to provide a method for preparing a magnetic transition metal sulfide adsorbent material, comprising the following steps: Under a protective atmosphere, the sulfur source and Mo-MOF were calcined at 1000℃~1100℃. The ligands in the Mo-MOF underwent carbonization, forming a porous carbon matrix. Simultaneously, the sulfur source and Mo… 3+ A sulfidation reaction occurs to form MoS2 particles, which are embedded in a porous carbon matrix to obtain MoS2 / C. Fe3O4 magnetic nanoparticles are loaded onto the surface of MoS2 / C using a chemical co-precipitation method to obtain a magnetic transition metal sulfide adsorbent material.

[0008] Preferably, the mass ratio of sulfur source to Mo-MOF is 1 to 5:1. If the sulfur source is too small, the molybdenum in the Mo-MOF cannot be completely converted into MoS2; if the sulfur source is too large, a large amount of sulfur will condense and deposit on the surface of the generated MoS2 nanosheets or in the pores of the carbon matrix, blocking the pores and covering the active sites. More preferably, the mass ratio of sulfur source to Mo-MOF is 5:1.

[0009] It should be noted that during the sulfidation reaction, the fragile Mo in the Mo-MOF is first destroyed. 3+ -N coordinate bonds completely disassemble the MOF framework, releasing the Mo... 3+ Ions and imidazole ligands; imidazole ligands undergo carbonization under a high-temperature inert atmosphere to form a porous carbon matrix with high specific surface area; free Mo 3+ S produced by the decomposition of sulfur source 2- Rapid bonding forms MoS2 nanoparticles, which are uniformly embedded in the porous carbon matrix, forming a MoS2 / C composite material.

[0010] Preferably, the mass ratio of MoS2 / C to Fe3O4 magnetic nanoparticles is 3 to 4:1.

[0011] Preferably, the sulfur source is thiourea.

[0012] The preferred method for chemical coprecipitation is as follows: MoS2 / C was dispersed in water, and Fe was added sequentially. 3+ Salt and Fe 2+Salt was used to load Fe3O4 magnetic nanoparticles onto the MoS2 / C surface under an inert atmosphere, with the pH adjusted to 9–11 and the reaction stirred. This yielded a magnetic transition metal sulfide adsorbent material.

[0013] Preferably, Fe 3+ Fe in salt 3+ with Fe 2+ Fe in salt 2+ The molar ratio is 0.5 to 1:1.

[0014] Preferably, the time used in the chemical coprecipitation method is 0.5 h to 2 h.

[0015] Preferably, Fe 3+ The salt is ferric chloride hexahydrate; Fe 2+ The salt is ferrous chloride tetrahydrate.

[0016] Preferably, the calcination method is Joule heating, and the calcination time is 10 minutes.

[0017] Preferably, the specific preparation method of Mo-MOF is as follows: Using molybdenum source and imidazole as raw materials, the molybdenum source and imidazole were subjected to a hydrothermal reaction at 100℃~110℃ in an aqueous system to obtain Mo-MOF.

[0018] Preferably, the molar ratio of molybdenum source to imidazole is 2 to 3:1.

[0019] Preferably, the hydrothermal reaction time is 24 hours.

[0020] Preferably, the molybdenum source is molybdenum trioxide.

[0021] A second objective of this invention is to provide a magnetic transition metal sulfide adsorbent material, which is prepared by the above-described preparation method.

[0022] Magnetic transition metal sulfide adsorbent materials are carbon-based materials loaded with transition metal sulfide nanorods and uniformly distributed Fe3O4 nanoparticles, exhibiting excellent adsorption / reduction activity, magnetic separation characteristics, and photoresponse characteristics.

[0023] Preferably, the transition metal sulfide nanorods have a diameter of 1 μm to 2 μm and a length of 4 μm to 5 μm.

[0024] The third objective of this invention is to provide an application of a magnetic transition metal sulfide adsorbent as a gold adsorbent for targeted adsorption of gold in gold-containing wastewater.

[0025] The preferred and specific application methods are as follows: Magnetic transition metal sulfide adsorbent material was added to gold-containing wastewater for adsorption.

[0026] Preferably, the concentration of the gold-containing wastewater is 50 mg / L to 2500 mg / L, and the ratio of the magnetic transition metal sulfide adsorbent material to the gold-containing wastewater is 1 mg: 2 mL to 4 mL.

[0027] Preferably, the adsorption temperature is 280K~320K. Compared with the prior art, the present invention has the following technical effects: 1. This invention uses Mo-MOF as a precursor, and calcines Mo-MOF and a sulfur source to form a conductive porous carbon matrix; simultaneously, the sulfur source and Mo... 3+ A sulfidation reaction occurs, forming highly stable MoS2 particles, which act as adsorbents for Au. 3+ The core active component is MoS2; and the porous carbon matrix encapsulates the MoS2 nanoparticles, effectively preventing direct contact between water molecules and the surface of the MoS2 particles, resulting in MoS2 / C. Then, Fe3O4 is loaded onto the MoS2 / C surface, endowing the material with magnetic and photoresponsive properties, allowing it to rapidly separate from water within minutes using an external magnetic field; and utilizing its own photothermal conversion capability to enhance the material's adsorption capacity; ensuring efficient and selective adsorption of Au in water. 3+ At the same time, it solved the technical problem of framework hydrolysis and collapse of MOFs in aquatic environments due to unstable coordination bonds.

[0028] 2. This invention constructs a transition metal sulfide adsorbent material with high specific surface area, rich in selective sulfur sites, and possessing reducing, photoresponsive, and magnetic properties based on MOF template-directed transformation; it can achieve adsorption of Au in water. 3+ An integrated synergistic process of adsorption-reduction-magnetic separation-photoresponse. Leveraging the abundant porous structure and large specific surface area of ​​MOF materials, and using S as the active site, a highly efficient and selective adsorption process is established; utilizing the strong reducing properties of MoS2, adsorbed Au can be... 3+ The material is directly reduced to elemental Au, achieving a one-step "adsorption-reduction" process. After adsorption, the loaded Fe3O4 particles endow the material with magnetic and photoresponsive properties, enabling rapid separation from water. Simultaneously, the photothermal conversion capability of Fe3O4 enhances the material's adsorption capacity, meeting the practical application requirements for gold resource recovery. This invention provides a highly efficient and sustainable solution for gold resource recovery.

[0029] 3. The magnetic transition metal sulfide adsorbent material prepared by this invention contains abundant selective sulfur sites, which can improve the adsorption capacity for Au. 3+ Its selective adsorption capacity reduces interference from coexisting ions, while its reducing properties allow for reasonable regulation of Au. 3+The reduction process ensures the adsorption capacity and adsorption rate of the material; the endowment of photoresponsive magnetism enables the material to achieve magnetic separation and photoregeneration, further improving the material's practicality and recyclability.

[0030] 4. This invention achieves a synthesis speed on the order of minutes using a Joule heating instrument, improving synthesis efficiency and reducing the synthesis cycle. Compared with the traditional tube furnace method, it significantly improves synthesis efficiency and reduces energy consumption. The preparation method of this invention is simple and the conditions are controllable, making large-scale production possible. Attached Figure Description

[0031] Figure 1 The images show SEM and EDS images of MoS2 / C-1000@Fe3O4 prepared in Example 1 at different magnifications. Among them, (a) is the SEM image at 5 μm magnification; (b) is the SEM image at 1 μm magnification; (c) is the Fe element distribution map; (d) is the O element distribution map; (e) is the Mo element distribution map; and (f) is the S element distribution map.

[0032] Figure 2 The graph shows the adsorption capacity of MoS2 / C on Au(Ⅲ) solution prepared under different parameter conditions in Comparative Example 2.

[0033] Figure 3 The graph shows the adsorption capacity of MoS2 / C-1000@Fe3O4 on Au(Ⅲ) solution prepared under different parameter conditions in Example 2.

[0034] Figure 4 The graph shows the adsorption capacity of MoS2 / C-1000@Fe3O4 on Au(Ⅲ) solution prepared under different parameter conditions in Example 3.

[0035] Figure 5 The image shows a physical sample of the magnetic properties of MoS2 / C-1000@Fe3O4 prepared in Example 1.

[0036] Figure 6 Isothermal adsorption curves of MoS2 / C-1000@Fe3O4 prepared in Example 1 at different temperatures.

[0037] Figure 7 The graph shows the adsorption capacity of MoS2 / C-1000@Fe3O4 prepared in Example 1 under different pH conditions.

[0038] Figure 8 The graph shows the adsorption capacity of MoS2 / C-1000@Fe3O4 prepared in Example 1 under light and under darkness.

[0039] Figure 9The images show the MoS2 / C-1000@Fe3O4 prepared in Example 1 before and after adsorption; where (a) is MoS2 / C-1000@Fe3O4 before adsorption and (b) is MoS2 / C-1000@Fe3O4 after adsorption.

[0040] Figure 10 The images show the physical images of the Au(III) solution before and after adsorption by MoS2 / C-1000@Fe3O4 prepared in Example 1; where (a) is the Au(III) solution before adsorption and (b) is the Au(III) solution after adsorption.

[0041] Figure 11 The selective adsorption and affinity diagrams of MoS2 / C-1000@Fe3O4 prepared in Example 1 on Au(Ⅲ) solutions containing impurity ions are shown; where (a) is the selective adsorption diagram of different ions and (b) is the affinity diagram of different ions. Detailed Implementation

[0042] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings.

[0043] Unless otherwise specified, all reagents used in this invention are commercially available, and all methods used are conventional techniques in the art.

[0044] Example 1 A method for preparing a magnetic transition metal sulfide adsorbent material includes the following steps: Step 1: Preparation of Mo-MOF: In a 250 mL double-necked flask, add 3.5 g of molybdenum trioxide and 100 mL of deionized water, and stir at room temperature for 20 min until the mixture is homogeneous. Then, add 1.66 g of imidazole and stir for 20 min until the mixture is homogeneous to obtain a uniformly dispersed solution.

[0045] The mixed solution was transferred to a constant temperature oil bath, and the oil bath temperature was set to 110℃. The mixture was stirred continuously at 240 rpm for 24 h, and reflux was carried out with cooling water. After the reaction was completed, the mixture was naturally cooled to room temperature. The white precipitate in the mixed solution was separated by vacuum filtration. The precipitate was washed with deionized water and the washing was repeated three times to remove impurities. Finally, the washed white solid was transferred to a vacuum drying oven and dried at 80℃ for 24 h. After grinding, Mo-MOF was obtained.

[0046] Step 2, Preparation of MoS2 / C: Thiourea and Mo-MOF were placed at both ends of carbon paper and spread evenly; the mass ratio of Mo-MOF to thiourea was 1:5. The carbon paper containing thiourea and Mo-MOF was then placed in a tube furnace. Before starting the Joule heating program, argon gas was continuously introduced into the Joule furnace for 30 minutes, maintaining a stable argon flow rate. This process was repeated three times to remove air from the Joule furnace, creating an inert protective atmosphere for subsequent high-temperature in-situ sulfidation and to check the airtightness of the apparatus. After removing the air, the Joule heating program was set to: temperature 1000℃, heating rate 500℃ / s. The tube furnace was heated under argon protection and calcined for 10 minutes. After natural cooling to room temperature, the black product was ground into a fine powder to obtain MoS2 / C.

[0047] Step 3: Preparation of magnetic transition metal sulfide adsorbent materials: In a 25 mL single-necked flask, add 100 mg of MoS2 / C and 12.5 mL of deionized water, stir for 10 min, then add 0.067 g of ferric chloride hexahydrate and 0.069 g of ferrous chloride tetrahydrate, stir for 15 min, and obtain a mixture.

[0048] Nitrogen gas was introduced into the mixture for 5 minutes to remove oxygen. Then, 2M NaOH was added to adjust the pH of the mixture to 10, and the mixture was stirred for 1 hour. The reactants were centrifuged at 2000 r / min for 30 minutes and then dried in a vacuum drying oven at 75℃ for 12 hours. After grinding, a magnetic transition metal sulfide adsorbent material was obtained, denoted as MoS2 / C-1000@Fe3O4.

[0049] The surface morphology of the magnetic transition metal sulfide adsorbent material prepared in Example 1 was analyzed, and the results are as follows: Figure 1 As shown.

[0050] like Figure 1 As shown in (a) and (b), the MoS2 / C-1000@Fe3O4 prepared in Example 1 is a dense structure composed of layered stacking, with a large number of Fe3O4 particles embedded both internally and on the surface, with a diameter of approximately 1.1 μm and a length of approximately 4.2 μm. Furthermore, through... Figure 1 As can be seen from (c) to (e), the S and Fe elements are attached to the material. The S element is formed by the reaction of H2S produced by the decomposition of thiourea with MOF; the Fe element is synthesized by the co-precipitation of ferric chloride hexahydrate and ferrous chloride tetrahydrate.

[0051] The photoresponsive magnetic MoS2 / C-1000@Fe3O4 adsorbent material derived from MOF templates effectively inherits the framework topological characteristics of MOF. Simultaneously, through the in-situ intercalation of Fe3O4 nanoparticles onto the MOF, the active sites are fully diffused, enabling the material to effectively adsorb Au.3+ The recycling effect has been enhanced.

[0052] Comparative Example 1 A method for preparing a transition metal sulfide adsorbent material includes the following steps: The difference from Example 1 is as follows: Fe3O4 was not loaded on MoS2 / C.

[0053] Step 1: Preparation of Mo-MOF: In a 250 mL double-necked flask, add 3.5 g of molybdenum trioxide and 100 mL of deionized water, and stir at room temperature for 20 min until the mixture is homogeneous. Then, add 1.66 g of imidazole and stir for 20 min until the mixture is homogeneous to obtain a uniformly dispersed solution.

[0054] The mixed solution was transferred to a constant temperature oil bath, and the oil bath temperature was set to 110℃. The mixture was stirred continuously at 240 rpm for 24 h, and reflux was carried out with cooling water. After the reaction was completed, the mixture was naturally cooled to room temperature. The white precipitate in the mixed solution was separated by vacuum filtration. The precipitate was washed with deionized water and the washing was repeated three times to remove impurities. Finally, the washed white solid was transferred to a vacuum drying oven and dried at 80℃ for 24 h. After grinding, Mo-MOF was obtained.

[0055] Step 2, Preparation of MoS2 / C: Mo-MOF and thiourea were placed at both ends of carbon paper and spread evenly; the mass ratio of Mo-MOF to thiourea was 1:5. The carbon paper containing thiourea and Mo-MOF was then placed in a tube furnace. Before starting the Joule heating program, argon gas was continuously introduced into the Joule furnace for 30 minutes, maintaining a stable argon flow rate. This process was repeated three times to remove air from the Joule furnace, creating an inert protective atmosphere for subsequent high-temperature in-situ sulfidation and to check the airtightness of the apparatus. After removing the air, the Joule heating program was set to: temperature 1000℃, heating rate 500℃ / s. The tube furnace was heated under argon protection and calcined for 10 minutes. After natural cooling to room temperature, the black product was ground into a fine powder to obtain MoS2 / C.

[0056] Comparative Example 2 A method for preparing a transition metal sulfide adsorbent material is basically the same as that of Comparative Example 1, except that the mass ratio of Mo-MOF and thiourea is different, as shown in Table 1.

[0057] Table 1. Optimized parameters for preparing MoS2 / C To investigate the effect of sulfur source doping on the adsorption of gold ions from gold-containing solutions by MoS2 / C, the corresponding MoS2 / C was prepared according to the optimized conditions in Table 1. The gold-containing solutions were then adsorbed to measure the change in Au(III) concentration before and after adsorption, and the adsorption capacity of the corresponding MoS2 / C was evaluated. The results are shown below. Figure 2 As shown.

[0058] like Figure 2 As shown, the adsorption capacity of the prepared MoS2 / C for Au(III) increases with the increase of Mo-MOF content. When the mass ratio of Mo-MOF to thiourea is 1:5, the adsorption capacity of MoS2 / C for Au(III) reaches its maximum value, and the adsorption capacity remains basically unchanged when the amount of Mo-MOF is further increased. This shows that this ratio helps MoS2 / C form more effective adsorption sites. Therefore, a mass ratio of Mo-MOF to thiourea of ​​1:5 is selected as the optimal ratio for preparing MoS2 / C.

[0059] Example 2 A method for preparing a magnetic transition metal sulfide adsorbent material is basically the same as that in Example 1, except that the mass ratio of Mo-MOF and thiourea is different, as shown in Table 2.

[0060] Table 2 Optimization conditions for preparing MoS2 / C To investigate the effect of sulfur source doping on the formation of MoS2 / C, and thus on the effect of magnetic transition metal sulfide adsorbent materials on the adsorption of gold ions in gold-containing solutions, corresponding magnetic transition metal sulfide adsorbent materials were prepared according to the optimized conditions of parameters in Table 2. The changes in Au(III) concentration before and after adsorption were measured by adsorbing gold-containing solutions, and the adsorption capacity of the corresponding magnetic transition metal sulfide adsorbent materials was evaluated.

[0061] The specific adsorption test results are as follows: Weigh 5 mg of the magnetic transition metal sulfide adsorbent material prepared in Example 2 and add it to 20 mL of Au(III) solution with a concentration of 1000 mg / L. Shake in a constant temperature shaking oven at 303 K for 12 h at a rotation speed of 180 rpm. After adsorption equilibrium, filter the sample using a needle filter and a 0.22 μm polyethersulfone membrane. Use a ContrAA 700 high-resolution continuous light source atomic absorption spectrometer to determine the change in Au(III) concentration before and after adsorption. The results are as follows: Figure 3 As shown.

[0062] like Figure 3As shown, the adsorption capacity of the prepared magnetic transition metal sulfide adsorbent material for Au(III) increases with the increase of Mo-MOF content. When the mass ratio of Mo-MOF to thiourea is 1:5, the adsorption capacity of the magnetic transition metal sulfide adsorbent material for Au(III) reaches its maximum value, and the adsorption capacity remains basically unchanged when Mo-MOF is further increased. This indicates that this ratio helps the magnetic transition metal sulfide adsorbent material form more effective adsorption sites. Therefore, a mass ratio of Mo-MOF to thiourea of ​​1:5 is selected as the optimal ratio for preparing the magnetic transition metal sulfide adsorbent material.

[0063] Example 3 A method for preparing a magnetic transition metal sulfide adsorbent material is basically the same as that in Example 1, except that the mass of ferric chloride hexahydrate and ferrous chloride tetrahydrate used to prepare Fe3O4 is different, as shown in Table 3.

[0064] Table 3 Optimized parameters for Fe3O4 preparation To investigate the effects of the mass of ferric chloride hexahydrate and ferrous chloride tetrahydrate used in the preparation of Fe3O4 on the magnetic properties of the magnetic transition metal sulfide adsorbent and its adsorption of gold ions in gold-containing solutions, corresponding magnetic transition metal sulfide adsorbents were prepared according to the optimized parameters in Table 3. The changes in Au(III) concentration before and after adsorption were measured by adsorbing gold-containing solutions to evaluate the adsorption capacity of the corresponding magnetic transition metal sulfide adsorbents. Simultaneously, the magnetic properties were tested, such as… Figure 4 As shown.

[0065] from Figure 4 As can be seen from the data, the magnetic transition metal sulfide adsorbent materials prepared under parameters 1 and 2 have good adsorption performance for Au(III), but are not magnetic; therefore, 0.067 g of ferric chloride hexahydrate and 0.069 g of ferrous chloride tetrahydrate were selected as the optimal ratio for synthesizing Fe3O4.

[0066] Test 1.

[0067] The magnetic properties of MoS2 / C-1000@Fe3O4 prepared in Example 1 were tested, and the specific testing method is as follows: The MoS2 / C-1000@Fe3O4 prepared in Example 1 was placed in a test tube, inverted, and suspended in the air. A magnet was brought close to the bottom of the test tube, and the result was as follows. Figure 2 As shown.

[0068] like Figure 2 As shown, MoS2 / C-1000@Fe3O4 is attracted to the bottom of the test tube due to its magnetism and does not sink, indicating that the magnetic transition metal sulfide adsorbent material prepared in the embodiments of the present invention has obvious magnetism.

[0069] Test 2.

[0070] Isothermal adsorption test.

[0071] 5 mg of MoS2 / C-1000@Fe3O4 was added as an adsorbent to 20 mL of Au(III) solutions of different concentrations. The solutions were shaken at 180 rpm for 12 h in a constant temperature shaking incubator at 303 K. The initial concentrations of the Au(III) solutions were 50 mg / L, 200 mg / L, 400 mg / L, 800 mg / L, 1000 mg / L, 1600 mg / L, 2000 mg / L, and 2500 mg / L. After adsorption equilibrium, the samples were filtered using a needle filter and a 0.22 μm polyethersulfone membrane to obtain the supernatant. The change in Au(III) concentration before and after adsorption was determined using a ContrAA 700 high-resolution continuous light source atomic absorption spectrometer.

[0072] like Figure 3 As shown, at 288.15 K, the adsorption capacity of MoS2 / C-1000@Fe3O4 for Au(III) is 4090 mg / L; at 303.15 K, the adsorption capacity of MoS2 / C-1000@Fe3O4 for Au(III) is 3873 mg / L; and at 318.15 K, the adsorption capacity of MoS2 / C-1000@Fe3O4 for Au(III) is 6258 mg / L. It can be seen that the adsorption capacity of the magnetic transition metal sulfide adsorbent material prepared in the embodiments of the present invention for Au(III) increases with increasing temperature.

[0073] Adsorption tests under different pH conditions.

[0074] Seven 20 mL solutions of Au(III) with an initial concentration of 50 mg / L were prepared, and the pH of the Au(III) solutions was adjusted sequentially to 1, 2, 3, 4, 5, 6, and 7. 5 mg of MoS2 / C-1000@Fe3O4 was added to each Au(III) solution at different pH values, and the mixture was shaken at a constant speed of 180 rpm for 1 hour in a constant-temperature shaker at 303 K to ensure adsorption equilibrium was reached. After adsorption, the mixture was filtered through a needle filter and a 0.22 μm polyethersulfone membrane to separate the solid-phase adsorbent, and the clear supernatant was collected. The residual Au(III) concentration in each supernatant was determined using continuous-wave atomic absorption spectrometry to evaluate the adsorption effect under different pH conditions.

[0075] like Figure 4 As shown, the MoS2 / C-1000@Fe3O4 adsorbent material still exhibits excellent adsorption of Au(III) in strong acid, with removal efficiencies approaching 100%.

[0076] Photoresponsive adsorption test.

[0077] Two 20 mL solutions of 1000 mg / L Au(III) were subjected to light-shielding and light-irradiation treatments, respectively. The light-irradiation treatment involved adding 5 mg of MoS2 / C-1000@Fe3O4 to 20 mL of 1000 mg / L Au(III) solution under visible light irradiation with a xenon lamp and then refluxing. After the MoS2 / C prepared in Comparative Example 1 was adsorbed to equilibrium, the mixture was filtered through a needle filter and a 0.22 μm polyethersulfone membrane. The supernatant was collected, and the concentration of Au(III) ions in the supernatant was determined using a continuous light source atomic absorption spectrometer.

[0078] from Figure 5 It can be clearly seen that, under illumination, MoS2 / C-1000@Fe3O4, as an adsorbent, effectively removes Au from Au(III) solution. 3+ The adsorption capacity of the adsorbent is greater than that of the adsorbent for Au(III) solution under no light conditions. 3+ The adsorption capacity doubles. This indicates that the magnetic transition metal sulfide adsorbent material prepared in the embodiments of the present invention has a significant response to visible light.

[0079] Table 4. Comparison of adsorption capacities of MoS2 / C-1000@Fe3O4 prepared in Example 1 and MoS2 / C prepared in Comparative Example 1 under shading and light irradiation treatments. As shown in Table 4, without light treatment, the adsorption capacity of MoS2 / C prepared in Comparative Example 1 for Au(III) ions is higher than that of MoS2 / C-1000@Fe3O4 prepared in Example 1. This is because although the addition of Fe3O4 endows the material with magnetism and photoresponsiveness, it easily blocks the adsorption sites of the material, thus leading to a decrease in the adsorption capacity of MoS2 / C-1000@Fe3O4 for Au(III) ions. After light treatment, compared with the MoS2 / C prepared in Comparative Example 1, the adsorption capacity of MoS2 / C-1000@Fe3O4 prepared in Example 1 for Au(III) ions is significantly improved. This is because the photothermal conversion ability of Fe3O4 significantly enhances the adsorption capacity of the material after light treatment.

[0080] Comparison test before and after adsorption.

[0081] 20 mg of MoS2 / C-1000@Fe3O4 was added as an adsorbent to 100 mL of a 1 g / L Au(III) solution, and the mixture was shaken at 180 rpm for 12 h in a constant temperature shaking oven at 303 K. After adsorption equilibrium, the adsorbed solid material was separated from the adsorbent solution using a vacuum filter. The adsorbed solid material was then dried in a vacuum drying oven at 75°C to obtain the adsorbed solid material, as shown below. Figure 6 As shown.

[0082] from Figure 6 The color change of the material before and after adsorption can be clearly observed. Figure 6 In the image (a), MoS2 / C-1000@Fe3O4 is shown before adsorption. Figure 6 (b) in the figure represents the adsorbed MoS2 / C-1000@Fe3O4.

[0083] from Figure 7 The color change of the adsorption solution before and after adsorption can be clearly observed. Figure 7 (a) in the image is the Au(III) solution before adsorption, which is light yellow in color; Figure 7 (b) shows the Au(III) solution after adsorption, which is essentially colorless and transparent. This indicates that the magnetic transition metal sulfide adsorbent material prepared in this embodiment of the invention effectively adsorbs Au(III) from the Au(III) solution. 3+ It has obvious adsorption properties.

[0084] Selective adsorption test.

[0085] 5 mg of MoS2 / C-1000@Fe3O4 was added as an adsorbent to 20 mL of K. + Ca 2+ Ni 2+ Cu 2+ Cd 2+ Zn 2+ and Au 3+ A mixed solution of seven ions, each with a concentration of 100 mg / L, was prepared. The solution was then shaken in a 30°C shaking incubator for 12 hours to reach adsorption equilibrium. After filtration through a needle filter and a 0.22 μm polyethersulfone membrane, the supernatant was collected. The concentration of each component ion in the supernatant was determined using a continuous-wave atomic absorption spectrometer. MoS2 / C-1000@Fe3O4 and Au 3+ Ions are evaluated using the partition coefficient (Kd), and the Kd value is an important indicator of the selectivity of the adsorbent. A Kd value of 1.0 × 10⁻⁶ is used. 5 mL / g is a key parameter that determines the excellent selectivity of an adsorbent.

[0086] like Figure 6 As shown, in the presence of K + Ca2+ Ni 2+ Cu 2+ Cd 2+ Zn 2+ and Au 3+ In a mixed solution of ions, the adsorbent only exhibits a high adsorption concentration for gold ions, and a lower adsorption concentration for K ions. + Ca 2+ Ni 2+ Cu 2+ Cd 2+ and Zn 2+ The adsorption concentration is low; gold ions can be completely separated from other metal ions; this shows that the adsorbent material prepared in the examples still has excellent selective adsorption of Au(III) in complex gold-containing solutions.

[0087] Test 3.

[0088] Using MoS2 / C-1000@Fe3O4 from Example 1 as an adsorbent for Au-containing... 3+ The solution was subjected to an adsorption test, and the specific adsorption test method is as follows: Preparation of the adsorption solution: Weigh 4.082 g of HAuCl4 and dissolve it in 500 mL of ultrapure water using ultrasonication. Transfer the solution to a 1 L volumetric flask, make up to volume, and shake well to obtain an Au concentration of 2.0 g / L. 3+ The stock solution is stored in brown glass bottles in a dark environment.

[0089] Measurement of Au 3+ Standard curve of the solution: Au diluted with 1% HNO3 solution 3+ Stock solutions were prepared sequentially at concentrations of 2 mg / L, 4 mg / L, 6 mg / L, 8 mg / L, and 10 mg / L for Au. 3+ Standard solution. Absorbance was measured using a continuous-light source atomic absorption spectrometer, expressed as Au. 3+ The concentration of the standard solution is plotted on the x-axis, and the absorbance on the y-axis, to obtain Au. 3+ Standard curve of the solution.

[0090] Au in actual samples 3+ Concentration determination: Au in the water sample was determined using a continuous light source atomic absorption spectrometer. 3 + Absorbance, calculated based on the standard curve (Au) 3+ Concentration, and used to evaluate the adsorbent's effect on Au. 3+ The removal effect was assessed. All experiments were conducted three times, and the final data was the average of the three experiments.

[0091] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range, as well as any value between the two endpoints, can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described in this invention to avoid redundancy. Although preferred embodiments of this invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments, and all such changes and modifications fall within the scope of this invention.

[0092] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. If these modifications and variations fall within the scope of equivalents of this invention, then this invention also intends to include these modifications and variations.

Claims

1. A method for producing a magnetic transition metal sulfide adsorbent material, characterized by, The method comprises the following steps: Under a protective atmosphere, the sulfur source and the Mo-MOF are calcined at 1000-1100°C, the ligand in the Mo-MOF is carbonized to form a porous carbon matrix, and at the same time, the sulfur source reacts with Mo 3+ to form MoS2 particles, which are embedded in the porous carbon matrix to obtain MoS2 / C; The magnetic transition metal sulfide adsorbent material is prepared by the method of claim 1-7.

2. The method for preparing the magnetic transition metal sulfide adsorbent material according to claim 1, characterized in that, The mass ratio of the sulfur source and the Mo-MOF is 1-5:

1. The mass ratio of the MoS2 / C and the Fe3O4 magnetic nanoparticles is 3-4:

1.

3. The method of claim 1, wherein the magnetic transition metal sulfide adsorbent material is prepared by a method comprising: providing a transition metal oxide; and reacting the transition metal oxide with a sulfur source to form the magnetic transition metal sulfide adsorbent material. The specific operation of the chemical co-precipitation method is as follows: MoS2 / C was dispersed in water, and Fe 3+ salt and Fe 2+ salt, under the protection of inert atmosphere, the pH was adjusted to 9-11, the reaction was stirred, and Fe3O4 magnetic nanoparticles were loaded on the surface of MoS2 / C to obtain a magnetic transition metal sulfide adsorbent.

4. The method of claim 3, wherein the magnetic transition metal sulfide adsorbent material is prepared by a method comprising: Fe 3+ Fe in the salt 3+ with Fe 2+ Fe in the salt 2+ in a molar ratio of 0.5-1 : 1 ; Fe 3+ The salt is ferric chloride hexahydrate; Fe 2+ The salt is ferrous chloride tetrahydrate.

5. The method of claim 1, wherein the magnetic transition metal sulfide adsorbent material is prepared by a method comprising: providing a transition metal oxide; and reacting the transition metal oxide with a sulfur source to form the magnetic transition metal sulfide adsorbent material. The calcination mode is Joule heating, and the calcination time is 10 min; the sulfur source is thiourea.

6. The method of claim 1, wherein the magnetic transition metal sulfide adsorbent material is prepared by a method comprising: providing a transition metal oxide; and reacting the transition metal oxide with a sulfur source to form the magnetic transition metal sulfide adsorbent material. The specific preparation method of the Mo-MOF is as follows: The Mo-MOF is obtained by hydrothermal reaction of a molybdenum source and imidazole at 100-110 DEG C in a water system; the molar ratio of the molybdenum source and imidazole is 2-3:

1.

7. The method of claim 6, wherein the magnetic transition metal sulfide adsorbent material is prepared by a method comprising: providing a transition metal oxide; and reacting the transition metal oxide with a sulfur source to form the magnetic transition metal sulfide adsorbent material. The molybdenum source is molybdenum trioxide.

8. A magnetic transition metal sulfide adsorbent material, characterized by, The magnetic transition metal sulfide adsorbent material is prepared by the method of claim 1-7.

9. Use of a magnetic transition metal sulfide adsorbent material as a gold adsorbent for targeted adsorption of gold in gold-containing wastewater, characterized in that, The magnetic transition metal sulfide adsorbent material is prepared by the method of claim 8.

10. Use of the magnetic transition metal sulfide adsorbent material according to claim 9 for the targeted adsorption of gold in gold-containing wastewater, characterized in that, The concentration of the gold-containing wastewater is 50-2500 mg / L, and the dosage ratio of the magnetic transition metal sulfide adsorbent material to the gold-containing wastewater is 1 mg:2-4 mL.

Citation Information

Patent Citations

  • Method for adsorbing precious metal complex ions in thiosulfate lixivium through molybdenum disulfide

    CN109706315A

  • Large specific surface dual-function magnetic adsorbent of crystalline diatomite loaded with nanometer Fe3O4 and preparation method thereof

    CN110013827A

  • Preparation method of magnetic Fe3O4@MOF composite material, product and application of magnetic Fe3O4@MOF composite material

    CN112108121A

  • Preparation method and application of magnetic PB / Fe3O4 / MoS2 composite material

    CN114768749A

  • Transition metal sulfide adsorbent as well as preparation method and application thereof

    CN119455886A